Cassava mosaic disease: incidence and yield performance of cassava cultivars in Zambia - Tembo, M.; Mataa, M.; Legg, James P.; Chikoti, Patrick Chiza; Ntawuruhunga, Pheneas (Springer, 2017)
Cassava is the main food crop for an estimated 30% of the population in Zambia where yields of 5.8 t/ha are some of the lowest of any major cassava-producing country. A study was conducted to characterize yield responses of Zambian cassava genotypes to cassava mosaic disease (CMD), as well as the relative susceptibilities to the causal viruses. CMD-free planting material of four improved cultivars (Mweru, Chila, Tanganyika and Kampolombo), four officially-promoted landraces (Nalumino, Kapumba, Bangweulu and Katobamphunta) and a locally popular landrace (Manyopola) were evaluated at a field site in Rufunsa District, Lusaka Province (central-eastern Zambia). Manyopola and Bangweulu were found to be susceptible and had high foliar incidences of CMD (97.5% and 74.7%, respectively) based on visual CMD symptoms with high severity scores (3.5, 3.5), whilst cv. Kampolombo was resistant (incidence 0.7%, severity 2.0). Mweru had the highest root yield (17.6 t ha-1 ) while Kapumba, the second most susceptible cultivar, had the lowest root yield (3.2 t ha-1 ). Significant inverse regression 2 relationships were demonstrated between CMD incidence and CMD severity with root yield. Using these regressions together with published data on cassava production and countrywide CMD incidence in Zambia, it was possible to estimate annual losses due to CMD at ca. US$ 51.7 million. Evidence for resistance to CMD amongst several of the improved cassava cultivars tested suggests that there is great potential for the effective control and management of CMD in Zambia, if these materials could be widely disseminated.